ANALISIS PENYEBAB DAN SOLUSI DINAMIKA KONFLIK ANTARA PTPN XIV DENGAN MASYARAKAT DI POLONGBANGKENG TAKALAR - Rahmadani, Nitra Anggun; Ainun Riskillah, Rara; Akbar Asdhar, Muhammad Rifat; Zalikhah Benz, Elysia; Nurkarmila,; Koto, Muhammad Raihan (Jurnal Legislatif, 2025)
The agrarian conflict in Polongbangkeng,Takalar, between the local community and PT Perkebunan Nusantara XIV (PTPN XIV), reflects a long-standing issue of land ownership inequality in Indonesia. The expansion of sugarcane plantations by PTPN XIV has displaced communities from lands historically cultivated through customary systems, resulting in social and economic vulnerability. This study aims to analyze the root causes of the prolonged land dispute and formulate legal solutions that ensure justice for both the community and the company. This research employs a normative legal method using statutory, case, and conceptual approaches. The findings reveal that the conflict stems from historical land claims by the community lacking formal legal documentation, whereas the company holds legal rights through a Land Use Right (HGU) permit. Proposed solutions include converting HGU into Land Management Rights (HPL), offering employment opportunities to affected residents, and providing legal education to strengthen community understanding of land rights. The novelty of this research lies in offering an integrative legal solution that balances corporate interests with social justice through participatory and sustainable agrarian law approaches. The study concludes that resolving agrarian conflicts requires legal clarity, community involvement, and the protection of historical land claims as part of achieving substantive justice. Keywords: Agrarian Conflict; PTPN XIV; Agrarian Law; HGU; HPL.